PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU DI FAVE HOTEL ADI SUCIPTO SOLO - Wahyu Ari Indriastuti; Lilik Kristanto (Riset Manajemen dan Akuntansi, 2016)
The development of Surakarta city as a city of culture has attracted many domestic and foreign tourists. This resulted in an increase in the hotel accommodation services. Fave Hotel guest solo research is always considered as given the importance of customers in the hospitality service activities that are managed by the company. Target or targets basically services that can meet customer expectations as users of the service. Residential customers who make repeated at the hotel is not only influenced by the quality of the room but also affected the quality of service. Good service quality will encourage consumers to re-occupancy. Hotels are examined in this study are Fave Hotel Solo. The procedure in the selection of the sample is non-probability sampling. The sampling method used in this study is to provide a questionnaire to guests who are staying at the Fave Hotel Adi Sucipto Solo. The results showed that the reliability of a positive effect on customer satisfaction, responsiveness positive effect on customer satisfaction, assurance / guarantee no positive effect on customer satisfaction, empathy positive effect on customer satisfaction, real (tangible) positive effect on customer satisfaction. Keywords: service quality, customer satisfaction.